PENGARUH AUDIT TENURE, ROTASI AUDIT, UKURAN KAP, DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT - Harry Budiantoro; Mohamad Royudin; Zainal Zawir Simon; Kanaya Lapae (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The goal of this study was to investigate the effect of exam duration, audit rotation, KAP size, and company size on audit quality empirically. This study's methodology is quantitative, and it employs logistic regression statistics from SPSS version 25. This study's population consists of production companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2017. The sample count is 80, with 240 samples collected between 2015 and 2017. According to the findings of the investigation, the inspection period has a positive and significant effect on the quality of the audit, the rotation of the audit has no effect on the quality of the audit, and the size of the company has no effect on audit quality.